Which specific golf skills are related to performance in skilled junior golfers? - Brozka, M.; Carson, H. J.; Komarc, M.; Zahalka, F.; Gryc, T. (International Journal of Golf Science, 2023)
Golf performance relies on success at several different skills. However, no previous studies have investigated multiple skills with a single research sample to discriminate key performance determinants. Furthermore, such research is limited concerning junior performances, which is an important phase in the transfer to the professional level. The aims of the study were to evaluate performance in a golf skills test battery, to identify any significant determinants of junior golfers` handicaps and to analyse the strength of associations between these skills. Sixteen skilled junior golfers performed golf skills tests that assessed putting to driving skills. Significant determinants of handicap were found for short shots from the bunker, short and long approach shots, driving accuracy and Combine test. Data imply that junior players should focus on shot accuracy for the fastest performance achievement, especially in short approach shots. However, for long-term performance development, it is important that driving and putting skills are developed to enable successful transition to cope with professional tournament demands.